The furies : violence and terror in the French and Russian Revolutions - Mayer, Arno J. (Princeton University Press, 2000)
This is a deliberately comparative study of violence and terror in the French and Russian revolutions. It points up a web of significant similarities which are explored and refined by analogic analysis.